Social Life Cycle Assessment in the Construction Industry: Systematic Literature Review and Identification of Relevant Social Indicators for Carbon Reinforced Concrete - Jana Gerta Backes; Marzia Traverso (Environment, Development and Sustainability, 2023)
This article deals with the application of social life cycle assessment (S-LCA) in the construction sector and explicitly focuses on carbon reinforced concrete (CRC). The publication consists of two parts: (1) a scientific literature review on the current implementation of S-LCA in the construction sector, and (2) the definition of the relevant social hotspots for the cradle-to-gate production of CRC. The literature review was conducted to provide a general overview and compare S-LCA studies in the construction sector; second, countries that provide the relevant input materials needed for CRC were identified. Analysis within the Social Hotspot Database (SHDB) helped determine the relative importance of the CRC supply country for each social category and subcategory. By developing a metric in the form of scores for each risk information, the potential risks indicated by the SHDB were measured. The results show that the focus of the indicators to be highlighted and further used in the indicator catalog is particularly in the area of labor rights and decent work in the health and safety subcategory. Missing data within the SHDB may result in a defined high average score and lead to a lower level of information. In the future, the identified 36 social indicators for CRC should be revised again in cooperation with the manufacturing industry. This study aims to further raise awareness in the construction sector of life-cycle-based sustainability that goes beyond the environmental aspects, and it is the first social hotspot screening using the SHDB for CRC.
Keywords: 330; Social life cycle assessment; S-LCA; Construction; Carbon reinforced concrete; Hotspot indicator catalog; Review